Review of rope‐based access methods for the forest canopy: safe and unsafe practices in published information sources and a summary of current methods. Issue 8 (11th May 2015) - Anderson, David L.; Koomjian, Will; French, Brian; Altenhoff, Scott R.; Luce, James
Summary: The availability of reliable information on tree climbing methods is critical for the development of canopy science and for the safety of workers accessing the forest canopy. To assess the breadth and quality of information contained in published climbing information, we performed searches in Web of Science and Google Scholar and evaluated 54 published sources on 10 predetermined criteria related to safety. We found a high incidence of unsafe recommendations that, if followed, could result in serious injury or death. Common errors included recommendations for equipment not suitable for tree climbing, advocating methods suitable for rock climbing but that can result in falls and trauma in tree climbing, and outdated information that no longer reflects best practices. We conclude by providing safety recommendations and a short review of tree climbing methods. This article thus serves as a guide for finding and interpreting best sources of methods for canopy access.